The orientation of the bibliometrics researchers in Indonesia using the Reference Publication Year Spectroscopy - Dayyanah Dayyanah; Cecep Ibrahim; Asrul Jaya (Berkala Ilmu Perpustakaan dan Informasi)
Introduction. Using references in a study as a source of information when conducting research is important. The purpose of this research is to determine the main references used by bibliometric researchers.